The Effectiveness of Using Mind Mapping Technique in Teaching Writing - Akbar, Gemilang Zein; Kasim, Usman; Aziz, Zulfadli (Language Circle: Journal of Language and Literature, 2024)
As one of the compulsory subjects in junior high school, it is undeniable that English must be taught to students. The objectives of this study are find out whether there is a significant difference in students’ writing achievement between students who are taught using the Mind Mapping Technique and those who are not taught using the Mind Mapping Technique at Pesantren Modern Al-Manar Bener Meriah. The sample was selected using a purposive sampling technique, where 15 of boys students were treated to an experimental group, and the other 15 of girl students were assigned as a control group. The data were collected from written tests (pre-test and post-test), they were analyzed using some formula: mean, standard deviation, and t-test. By comparing t-test score and t-table score, it shows that the result is 2.93 while the result of t-table at a level significance with = 0.05 is 2.160. It means that t-test score is higher than t-table score. It can be concluded that the students who were taught by using mind mapping technique achieve a better performance than those who did not. Therefore, when concentrating students’ writing becomes the goal of instruction, mind mapping should be utilized as an alternative teaching strategy.